2016
DOI: 10.1111/jam.13005
|View full text |Cite
|
Sign up to set email alerts
|

Live yeasts enhance fibre degradation in the cow rumen through an increase in plant substrate colonization by fibrolytic bacteria and fungi

Abstract: Distribution of this microbial additive could be an interesting tool to increase fibre digestion in the rumen and thereby improve cow feed efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 53 publications
(118 reference statements)
4
32
2
Order By: Relevance
“…However, the role of rumen fungi remains largely unexplored. Previous studies have reported that the rumen contained higher proportions of Ascomycota, Basidiomycota, and Neocallimastigomycota [51,52]. In this study, Aspergillus accounted for approximately 47% of the fungal population at D0 but declined to undetectable levels from D3 to D14, however, the amniotic fluid culture tested positive for Aspergillus flavus.…”
Section: Discussioncontrasting
confidence: 47%
“…However, the role of rumen fungi remains largely unexplored. Previous studies have reported that the rumen contained higher proportions of Ascomycota, Basidiomycota, and Neocallimastigomycota [51,52]. In this study, Aspergillus accounted for approximately 47% of the fungal population at D0 but declined to undetectable levels from D3 to D14, however, the amniotic fluid culture tested positive for Aspergillus flavus.…”
Section: Discussioncontrasting
confidence: 47%
“…This is supposedly done by consuming some of the oxygen in ruminal fluid, thus preventing toxicity to the ruminal bacterial and other strict anaerobes and allowing a better performance of these organisms on feed degradation (Newbold et al, 1996). The idea of enhancement of bacterial and fungal colonization of fibrous materials due to a diminished amount of oxygen has lasted until now (Chaucheyras-Durand et al, 2016). Other explanations for the in vivo mode of action is nutritional competition with autochthonous ruminal microbial species as well as the supply of nutrients (e.g.…”
Section: In Vivo Mode Of Action Of Saccharomyces In Livestockmentioning
confidence: 99%
“…A significant increase in digestion of NDF, ADF and hemicellulose was observed with S. cerevisiae NCDC42 culture at 1 ml kg −1 body weight (Tripathi and Karim ). Furthermore, Chaucheyras‐Durand et al () reported that Saccharomyces may indirectly promote microbial fibre degradation by stabilizing ruminal pH and increasing dry matter intake. Lascano et al () reported that supplementation of S. cerevisiae at 3·13 × 10 7 CFU per gram in lactating cows increased fibre digestibility, improved milk and fat contents and improved gastrointestinal tract microbial balance.…”
Section: Impact Of Feeding Single‐cell Fungi On Rumen Fermentation Acmentioning
confidence: 99%